Ways to Improve the Efficiency of ТіО2-based Photocatalysts (Review) - Mironyuk, I.F.; Soltys, L.M.; Tatarchuk , T.R.; Tsinurchyn , V.I. (Physics and Chemistry of Solid State, 2020)
Water and air pollutants pose a significant environmental problem worldwide and photocatalysis is one way to address this global issue. Photocatalytic degradation of toxic substances under the influence of visible electromagnetic radiation is widely used for wastewater treatment. The most promising method of pollutant removal is the use of photocatalysts based on titanium (IV) oxide, which are recognized as one of the most effective due to chemical resistance, non-toxicity and low cost. However, their practical application is limited by the rapid recombination of photogenerated charge carriers and the selective absorption of light in the UV region due to the large width of band gap. To solve this scientific and practical problem, it is necessary to modify the surface, for example, through metallic or nonmetallic doping, in order to increase its photocatalytic activity due to additional absorption in the visible range of the spectrum. This review presents an analysis of current research on ways to increase the efficiency of TiO2-based photocatalysts.